Using Well Logs Data in Logfacies Determination By Applying the Cluster Analysis technique for Khasib Formation, Amara Oil Field, South Eastern Iraq - Al-Baldawi, Buraq Adnan Hussein (Journal of Petroleum Research and Studies, 2016)
Reservoir facies determination is the most important job in oil industry which dominantly relies on the major properties of rocks. Fundamental properties of rocks are usually understood by their detailed description in the field (lithofacies analysis) and laboratory (petrofacies analysis). The facies (lithofacies and petrofacies) determination in most subsurface studies is impractical, due to lack of cores and cuttings. In such situations, where the wire line logs are the only data available, the logfacies or electrofacies are determined instead. In this study, the available logs (gamma ray, density,Neutron, and sonic logs) for four wells (Am-1, Am-4, Am- 5, and Am-6) were used to predicate logfacies of Khasib Formation in Amara oil field. Using Cluster Analysis in this study practiced the logfacies determination in each unit of khasib Formation in Amara oil Field using Interactive Petrophysics software. The types of input data into Interactive Petrophysics software to determine logfacies are available logs which are used to create 15 clusters and determine five groups of logfacies. In this paper, the vertical variations of logfacies for Khasib Formation are carried out based on five groups of logfacies. These groups of logfacies are classified based on responses of well logs after divided Khasib Formation into three units :( upper, middle and lower Khasib). In order to estimate the ratio of existence of logfacies, the histogram of logfacies was built for each unit of Khasib Formation in studied wells.